Histerectomía en las pacientes ingresadas en El Hospital San Vicente De Paúl En El Cantón Pasaje en el año 2012. - Sigsig Guayara, Karla (2015)
Hysterectomy is considered an invasive surgical procedure which is performed during or after childbirth is also indicated as operative treatment of complications that can be fatal to patients, making it impossible to control. Why the following research work he had performed the same general objective: To determine the characteristics of hysterectomy in patients admitted to the San Vicente de Paul hospital in the canton passage in 2012. Using a cross-sectional study research was conducted by reviewing 72 medical records that correspond to the universe of the study population using analytical and synthetic deductive study is divided into three phases.